Pelaksanaan dan Pengembangan Sumber Daya Tenaga Kependidikan - Egi Febrizon (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This study is intended to describe the implementation and development of the resources of educators in Madrasah Ibtidaiyah in Kerinci, including developing the competence of educators and improve the competence of personnel an educational institution. This is the study of the conceptual article. Data were collected using a literature review and documentation. The results of this study show: 1) competence development pattern of produce educators. The pattern of development of the competence of produce educators in Madrasah Ibtidaiyah in Kerinci general competencies, such as functional competencies, and other things the optimal, is enough is given to educational personnel such as education and training, workshops, training, functional training, structural position, and the development competence of IT. competency development Strategy 2) product educators in Madrasah Ibtidaiyah in Kerinci, such training is enough to power is given to a local optimum. 3) competency factors influencing the development of produce educators at the Madrasah Ibtidaiyah in Kerinci, i.e. internal factors such as: vision, mission, objectives, strategy of achievement of the objectives, nature and type of activities, and the type of technology used, as well as external factors such as government policies, the socio-cultural society, and the development of science and technology.